HADIH MAJA SEBAGAI MEDIA KOMUNIKASI PENGUATAN KELUARGA: STUDI PADA GAMPONG LADA, KECAMATAN MUTIARA TIMUR - syauqas rahmatillah (Lembaga Sepercenter, 2025)
Hadih maja is a traditional Acehnese oral expression that encompasses moral and spiritual values, playing a significant role in family communication in Gampong Lada, Kecamatan Mutiara Timur, Kabupaten Pidie. However, in recent decades, the use of hadih maja has significantly declined. This article aims to explore the role of hadih maja in family communication and identify strategies for its preservation. The research employs a qualitative approach with a case study methodology. Data were collected through in-depth interviews with family members in Gampong Lada and analyzed to identify patterns of hadih maja usage and the challenges faced. The findings indicate that although hadih maja is still used, its frequency has decreased, particularly among the younger generation. Therefore, it is recommended to implement revitalization efforts through cultural education and training for the youth to maintain the preservation of hadih maja as a valuable communication medium. These findings provide important insights into how to preserve traditional communication in the modern era and reinforce the role of local culture in everyday life.